EXAMINING THERMAL TOLERANCE AND PHYLOGENETIC CHARACTERISTICS OF JUVENILE ERYX JOHNII IN THE THAL DESERT (The Research of Medical Science Review, 2025)
Juvenile Eryx johnii (Indian Sand Boa) inhabit the Thal Desert, a region marked by intense heat, dryness, and limited prey availability — conditions that strongly challenge their survival. Compared to adults, juveniles show reduced thermal tolerance and are more prone to dehydration, making them vulnerable to climate-driven shifts in soil moisture and food availability. Their persistence relies on fossorial behaviors such as burrowing and refuge-seeking, which enable thermoregulation and protection from predators. Phylogenetic analyses classify Eryx johnii in the Erycinae group and trace its divergence back to the Miocene, highlighting adaptations suited to desert habitats. Anthropogenic threats — including illegal trade and exploitation for traditional medicine — further endanger this Near Threatened species. Filling knowledge gaps on juvenile ecology, thermal limits, and habitat use is vital for developing climate-resilient conservation strategies